CYCLOSPORINE-A REDUCES THE SEVERITY OF COLD-RESTRAINT-INDUCED GASTRIC-LESIONS - ROLE OF LEUKOCYTES - (:unkn) unknown (KARGER, 1995)
The objective of this study was to determine the role of cyclosporin A (CsA) on cold-restraint-induced gastric lesions. Animals were subjected to 3 h immobilization at 4 degrees C in plastic restraining devices following a starvation period of 48 h. Gastric samples were obtained for the measurement of myeloperoxidase (MPO) activity, an index of number of peroxidase positive cells and thiobarbituric acid-reactive substances (TBARS; lipid peroxidation). Animals were pretreated with CsA which is a potent immunosuppressant and inhibits ischemia/reperfusion-induced polymorphonuclear leukocyte (PMN) infiltration. Cold-restraint administration significantly elevated the tissue MPO activity and TEARS formation. CsA pretreatment significantly reduced the severity of cold-restraint-induced gastric lesions while attenuating the elevated MPO measurements observed during cold-restraint administration. Animals rendered neutropenic with antineutrophil serum (ANS) exhibited significantly less gastric mucosal injury normally observed after cold-restraint stress. Neither CsA nor ANS treatment effected the elevated TEAR levels, indicating that PMNs are not involved in the lipid peroxidation process observed after cold-restraint stress. In conclusion, the results of this study indicate that CsA is capable of inhibiting cold-restraint-induced gastric mucosal injury and can attenuate the cold-restraint-induced increases in gastric MPO measurements. Our results also indicate that PMNs may be the important mediators of cold-restraint-induced gastric lesions.
Keywords: CYCLOSPORINE A; MYELOPEROXIDASE; COLD RESTRAINT; POLYMORPHONUCLEAR LEUKOCYTES; MUCOSAL BLOOD-FLOW; RATS; STRESS; ADHESION; INJURY; NEUTROPHILS; ULCERATION; INHIBITION; SUPEROXIDE; VENULES